Are they looking for support? Mental health and trauma awareness as predictors of mental health help-seeking behaviour among young adults and adolescents in Bangladesh, Egypt, Ghana and the United Arab Emirates - Maxwell Peprah Opoku; Rahemeen Yusuf; Shakila Nur; Ebenezer Mensah Gyimah; Lilian Frimpomaa; Eleana Charalambous; Yasmin A. Salem; Mokhtar A. Elkayal; Aisha A. Abosrea; Tawasol Babiker; Mahra Murad Alblooshi; Erin September; et al. (BMC Public Health)
Abstract Background Mental health is increasingly recognized worldwide as a significant public health challenge. However, progress in developing interventions to address mental health burdens, particularly in non-Western countries, has been remarkably slow. This stagnation may be attributed to limited research on the underlying causes of mental health issues, such as trauma, as well as a lack of awareness regarding mental health disorders and help-seeking behaviours. The current study seeks to mainstream the understanding of mental health disorders by investigating the impact of trauma awareness and mental health disorders on the variance in help-seeking behaviours for mental health in non-Western contexts. This exploration aims to enhance the discourse on mental health initiatives and inform strategies for promoting mental health awareness and access to care in these regions. Methods A total of 2472 young adults (n = 1871) and adolescents (n = 601) were recruited from four countries (Bangladesh, n = 487; Egypt, n = 1070; Ghana, n = 695; and UAE, n = 217) to participate in this study. They completed three survey scales, namely, the Depression, Anxiety and Stress Scale, the Individual Trauma Identification and Management Scale and the Attitude toward Seeking Professional Psychological Help. Using the Statistical Package for Social Science version 29 and the Andrew Hayes PROCESS Model version 4.0, the data were subjected to hierarchical multiple regression, moderation and mediation analyses. Results Both trauma and mental health disorders collectively served as predictors of access to mental health help-seeking behaviour. Furthermore, mental health help-seeking behaviour was identified as a mediating factor in the relationship between trauma and mental health disorders. Conclusion This study recommends the establishment of mental health and trauma awareness programs specifically aimed at young adults and adolescents across these four countries. Additionally, a comprehensive discussion of the study’s implications is provided in detail.